Focused ultrasound for high-risk human papillomavirus infection-related low-grade cervical lesions: a prospective cohort study. (31st December 2022) - Wang, Wenping; Yao, Yuqin; Liu, Yujuan; Ren, Jiaojiao; Chen, Liming; Wang, Zhibiao; Zhou, Honggui
Abstract: Objectives: To assess the efficacy and safety of focused ultrasound (FU) for high-risk human papillomavirus (HR-HPV) infection-related cervical low-grade squamous intraepithelial lesions (LSIL). Methods: Of 185 patients who met the inclusion criteria for this prospective study from October 2020 to November 2021, 95 received FU and 90 were followed up only. At the six-month follow-up, the HR-HPV clearance and LSIL regression rates of the groups were compared and factors affecting HR-HPV clearance were analyzed. The safety and side effects of FU were evaluated. Results: No significant difference was found in the baseline clinical data between the two groups ( p  > 0.05). At the six-month follow-up, the HR-HPV clearance rates were 75.6% in the FU group and 25.6% in the observation group ( p  = 0.000). The LSIL regression rates were 89.5% in the FU group and 56.4% in the observation group ( p  = 0.000). Multivariate logistic regression analysis showed that the HR-HPV clearance rate in the FU group was 9.03 times higher than that in the observation group (95% confidence interval [CI], 3.75–21.73, p  = 0.000), and the clearance rate of single-type HR-HPV infections was 5.28 times higher than that of multi-type infections (95% CI, 1.83–15.23, p  = 0.002). The mean intraoperative bleeding was 1.8 ± 0.6 (1–3) mL; the mean intraoperative pain score was 2.6 ± 1.0 (1–6). Conclusions: For patients with HR-HPV infection-related histological LSIL, FU can eliminate HR-HPV infection and cause lesions to regress in a short time, with few adverse effects and good tolerance.